The Performance Analysis of Business Improvement Strategies using Financial Feasibility Approach Towards Education Startup: A Case Study of Compress Club - Hariadi, Rosihunal Ilmi (Proceedings International Conference on Education Innovation and Social Science, 2023)
Educated unemployment is becoming bigger every year in Indonesia. Soft skills and experience are preferred over educational background, but students lack those areas. Therefore, a skill development platform suitable to solve mismatching employment needs. Compress Club was established in 2021 as an education startup centered around its innovative mentoring system which incorporates interactive and progressive value, hoping to help high-achiever students gain a better soft skill and faster career preparation. Compress Club differentiated products to participate in programmes that students can to join; first year, middle year, and final year programmes during the university study. Based on the company's financial history from 2021 to 2023, the number of consumers fluctuated and decreased sometime, inconsistency happens through customer preference change based on market trends. This situation indicates Compress Club to create improvement strategies starting from forecasting appropriate programmes innovation until the readiness of strategies implementation in the future. For this reason, feasibility study is carried out from a financial perspective, analysing Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR), completed with risk assessment as a readiness of the business improvement strategies. The result concludes that Compress Club has the ability to perform with 5 years projection by implementing the programmes innovation as valid strategies in improving business performance. There is optimism that payback period reached within 11 months with an NPV of IDR1,850,499,938 and IRR of 130.15% surpass business feasibility criteria greater than Weighted Cost of Capital (WACC) value of 7.66%.